The Implementation of Multicultural Education Values: Strategies for Building a Moderate Attitude in Madrasahs - Tuala, Riyuzen Praja; Ilham, Muhammad; Pahlevi, Reza (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
Multicultural education in Indonesia has become an essential need amidst the diversity of ethnicity, culture, and religion. Madrasahs, as Islamic educational institutions, play a strategic role in integrating multicultural values to shape students' moderate attitudes. This study aims to explore the implementation of multicultural education values at Madrasah Imbos in Pringsewu and identify its impact on developing students' moderate attitudes. The research method used is qualitative with a case study approach. Data was collected through observation, in-depth interviews, and documentation to gain comprehensive insights into the educational process. The results of the study show that the integration of multicultural values into the curriculum, dialogue-based teaching methods, and student participation in extracurricular activities focused on diversity have successfully enhanced students' understanding of cultural differences. Approximately 80% of students demonstrated an improved moderate attitude after participating in the multicultural program, indicating the program's effectiveness. However, challenges in implementation include resistance from some students who struggle to accept these values and limited teaching resources that may hinder the program's sustainability. This study highlights the importance of continuous teacher training and competency development to address these challenges and ensure the successful implementation of multicultural education. By illustrating effective strategies in fostering moderate attitudes through multicultural practices, this research makes a significant contribution and can serve as a reference for other madrasahs in developing inclusive education policies. The findings are expected to strengthen educational efforts in nurturing harmony, understanding, and tolerance within a diverse society, thus promoting peaceful coexistence and mutual respect.